f(n) = f(n-2) + f(n - 1)
-->
You are saying that x = f(n), y = f(n + 1) solves the equation?
x = 1, y = 1 --> 1 - 1 - 1 = -1, YES
x = 1, y = 2 --> 1 - 2 - 4 = -5, NO
x = 2, y = 1 --> 4 - 2 - 1 = 1, YES
x = 3, y = 2 --> 9 - 6 - 4 = -1, YES
x = 5, y = 3 --> 25 - 15 - 9 = 1, YES
...OK, so you can prove this by induction:
Assuming that this is true for:
x = f(n), y = f(n-1), I'll call this P(n)
We can show that it is ALSO true for:
x = f(n + 1), y = f(n), I'll call this P(n + 1)
-->
P(n) implies the following:
(f(n))² - f(n) * f(n - 1) - (f(n - 1))² = ±1
Now I want to see if P(n + 1) holds, I'll do this by evaluating the LHS:
(f(n + 1))² - f(n + 1) * f(n) - (f(n))²
But I can write f(n + 1) in terms of f(n) and f(n - 1)
-->
(f(n) + f(n - 1))² - (f(n) + f(n - 1)) * f(n) - (f(n))²
--> now multiply things out
f²(n) + 2f(n)f(n - 1) + f²(n - 1) - f²(n) - f(n - 1)) * f(n) - f²(n)
--> collecting like terms this leaves:
f²(n - 1) + f(n)f(n - 1) - f²(n)
--> this looks VERY similar to the expression in P(n)
multiply by negative (switch the 1st and last term)
- (f²(n) - f(n)f(n - 1) - f²(n - 1))
But I know from my assumption that P(n) held, that this inside part is ±1
So I have:
-(±1) = -/+1, therefor P(n + 1) holds
So I have the following theorem:
P(n) -> P(n + 1)
That is, if x = f(n), y = f(n - 1) is a solution, then x = f(n + 1), y = f(n) is ALSO a solution. This is where you get your sequential Fibonacci numbers.
The only thing left to do (but I already did it above) is to prove the base case. Well the base case is n = 1 -->
x = f(1), y = f(0) --> x = 1, y = 1 --> proved to be true above
So you can say that P(1) --> P(n), for ALL n >= 1
since P(1) proves P(2), P(2) proves P(3)...etc, this is standard proof by Weak Induction.
Therefore yes you are correct that consecutive Fibonacci numbers are integer solutions. But we have by NO means shown that these are the ONLY integer solutions, but there are certainly infinitely many of them.